KEHIDUPAN ANAK JALANAN DAN EVALUASI MODEL PENANGANANNYA: STUDI KRITIS TERHADAP PENDEKATAN KEBIJAKAN SOSIAL ANAK JALANAN - Dwi Agustina (Universitas Pendidikan Ganesha, 2025)
Street children represent a vulnerable group that remains a significant social issue, including in the city of Yogyakarta. They live in public spaces under severe limitations socially, economically, and psychologically. This study aims to describe the lived experiences of street children in Yogyakarta and to evaluate the intervention models implemented by relevant stakeholders. Using a descriptive qualitative approach, data were collected through incidental sampling from three street child informants. Data were gathered through interviews and policy document analysis, and analyzed using Miles and Huberman’s interactive model. The findings indicate that the lives of street children are marked by instability and uncertainty. Key factors driving them to the streets include poverty, domestic violence, and the death of parents. Informal work such as busking and scavenging is commonly chosen, as it requires no formal skills or education many have dropped out of school or never attended at all. Meanwhile, the existing intervention models comprising prevention, outreach, rights fulfillment, and social reintegration remain largely top-down in nature. These models have yet to fully address the root causes of the issue and often fail to engage children as active participants. Therefore, a more participatory and sustainable social policy approach is urgently needed, so that interventions become not only administrative in nature but also genuinely transformative.